Integrated Transcriptomic and Proteomic Analysis in the Roadmap of the Xylem Development Stage in Populus tomentosa - Zhang, Chong; Zhang, Jiaxue; Liu, Yadi; Liu, Xiatong; Guo, Xiaorui; Li, Hui; Liu, Di; Lu, Hai (Frontiers in Plant Science, 2021)
Xylem development plays an important role in the wood formation of plants. In this study, we found that xylem development was a rapid thickening process characterized by initially rapid increases in the number of tracheary elements and fiber cells and the thickness of the secondary walls that later plateaued. Transcriptome analysis showed that the xylan and lignin biosynthetic pathways, which are involved in the early rapid thickening of the xylem, were mainly upregulated in the second month. The expression of a total of 124 transcription factors (TFs), including 28 NAC TFs and 31 MYB TFs, peaked in 2- and 3-month-old plants compared with 1-month-old plants. Based on previous studies and the key cis-acting elements secondary wall NAC-binding elements, secondary wall MYB-responsive elements, W-box and TGTG[T/G/C], 10 TFs related to xylem development, 50 TFs with unknown function, 98 cell wall biosynthetic genes, and 47 programmed cell death (PCD) genes were used to construct a four-layer transcriptional regulatory network (TRN) with poplar NAC domain TFs to characterize the transcriptional regulation of cell wall biosynthesis and PCD in Populus tomentosa. The proteome revealed that post-transcriptional modification may be widely involved in lignification development. Overall, our results revealed that xylem development is a rapid thickening process in P. tomentosa, and expression patterns varied temporally from cell division to cell death.